A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India - Trivedi, Jigneshkumar N.; Osawa, Masayuki; Vachhrajani, Kauresh D. (Zootaxa, 2016)
A new species of diogenid hermit crab, Diogenes chhapgari n. sp., is described on the basis of material collected during the crustacean faunal survey along the coastal areas of the Gujarat State, northwestern India. The new species is referred to the D. edwardsii (De Haan, 1849) species group and appears closest to D. singaporensis Rahayu, 2015. However, D. chhapgari n. sp. is distinguished from this species by the armature on the fourth segment of the antennal peduncle and carpus of the left cheliped.